(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: Utilizing magnesium and its alloys as degradable material for implant manufacturing is a currently hot topic. Even if first commercial implants are available, basic understanding is still missing how degradation is influenced by choice of alloy, implant design, production chain and individual biological environment. In particular, manufacturing can affect degradation and mechanical properties strongly. Thus, techniques extremely flexible in geometrical possibilities are needed to provide test specimens and final implant with constant properties. Technologies based on sintering are per se excellent candidates, because independent of size and design identical homogenous microstructures are guaranteed. Materials and Methods: In the current study, different alloy powders based on the systems Mg-Ca, Mg-Gd and Mg-Al-Zn in the size < 45 µm were used and mixed with polymeric binder to prepare filaments for Fused Filament Fabrication (FFF) and granules for Composite Extrusion Modelling (CEM). The optimization of the binder compositions was part of the study. In short paraffin waxes, stearic acid, polypropylene-copolymer-polyethylene and thermoplastic elastomer (TPE) were used, in ratios depending on if filaments or granules were produced. Test parts were printed, solvent debinded in hexane and further processed in a combined debinding and sintering hot wall furnace (MUT Advanced Heating GmbH, Jena, Germany). Sintering parameters were typically 4h at 615 °C under Ar at ambient pressure for Mg-Al-Zn alloys. Results and Discussion: Exemplarily, the results for Mg-8Al-1Zn powders are presented. Both, FFF and CEM led to reasonable printing results after sintering. Residual porosity was smaller 5 %, meaning only closed pores exist. Tensile tests of micro samples fabricated by FFF revealed UTS of 178 MPa and an elongation to fracture around 3%. The latter value shows that further improvement work should be done, even if the properties are already sufficient for many applications. Microscopy images display some delamination of the printed layers, which is probably the main reason for early fracture. Conclusion: This first study on sintering-based AM of Mg-alloys proves the feasibility of these technologies. However, additional work on the technical and scientific has to be performed in order to get optimized and reproducible results. Nevertheless, the potential of these techniques for individual parts and small series in combination with easy transfer to mass production techniques like metal injection moulding (MIM) is already recognized.